4D cardiac electromechanical activation imaging. (October 2019) - Grondin, Julien; Wang, Dafang; Grubb, Christopher S.; Trayanova, Natalia; Konofagou, Elisa E.
Abstract: Cardiac abnormalities, a major cause of morbidity and mortality, affect millions of people worldwide. Despite the urgent clinical need for early diagnosis, there is currently no noninvasive technique that can infer to the electrical function of the whole heart in 3D and thereby localize abnormalities at the point of care. Here we present a new method for noninvasive 4D mapping of the cardiac electromechanical activity in a single heartbeat for heart disease characterization such as arrhythmia and infarction. Our novel technique captures the 3D activation wave of the heart in vivo using high volume-rate (500 volumes per second) ultrasound with a 32 × 32 matrix array. Electromechanical activation maps are first presented in a normal and infarcted cardiac model in silico and in canine heart during pacing and re-entrant ventricular tachycardia in vivo. Noninvasive 4D electromechanical activation mapping in a healthy volunteer and a heart failure patient are also determined. The technique described herein allows for direct, simultaneous and noninvasive visualization of electromechanical activation in 3D, which provides complementary information on myocardial viability and/or abnormality to clinical imaging. Highlights: 4D Electromechanical Wave Imaging (EWI) was performed with high volume-rate ultrasound in normal and infarcted hearts. 4D Electromechanical activation mapping of the full heart can be performed non-invasively in humans. 3D Electrical and electromechanical activation are well correlated in-silico and in-vivo. Sinus rhythm, paced rhythm and ventricular tachycardia can be mapped with 4D EWI in a single heartbeat.